System Monitoring Consumption Household Electrical Energy IOT Based - Jifa Astrawarna, Iqbal; Hardyanto, R. Hafid; Wahyu Ciptadi, Prahenusa; Mohd Nawi, Mohd Nasrun (APPLIED SCIENCE AND TECHNOLOGY REASERCH JOURNAL, 2025)
Energy electricity used in a way Keep going continuously cause waste energy, while in development energy alternative need time so long that needed effort in savings energy with system new that can in a way direct applied public For save usage energy electricityMonitoring magnitude electricity distance Far or online need done use know condition real from A system power electricity. Monitoring must give information in a way complex the SMART concept (Specific, Measurable, Attainable, Relevant, Time-bound), namely specific, measurable, achievable attainable, relevant, and in range time Household Energy Consumption Monitoring System Based on Internet of Things (IoT) is an innovative solution to optimize energy management in household environments. This study aims to design and implement a system that utilizes IoT technology to measure, monitor, and analyze energy consumption on electronic devices in households.